The Law in front of the gene editing technique. CRISPR - Cárdenas Krenz, Ronald (Acta Bioethica, 2019)
The CRISPR genetic editing technique is one of the most extraordinary recent advances in biotechnology, whose scope is unsuspected. In this context, it is fundamental to analyze its repercussions in the field of the Human Rights, since as well as it can promote extraordinary advances for its better development, it can also generate new threats.